Structure and function of adenovirus type 12 defective virions. - Mak, I (1979)
Purified human adenovirus type 12 preparations contain defective virions with a lighter density. These defective virions were isolated, and their biological functions and DNA were characterized. They can induce early and late antigens in infected cells and tumors in newborn hamsters with similar efficiency as complete virions. The majority of the DNA molecules from light virions contain deletions mapping near 16% from the left-hand end of the genome. Mechanisms for the generation of these molecules are discussed.